EVALUASI PADA WEBSITE SRAGENKAB.GO.ID MENGGUNAKAN METODE WEB USABILITY EVALUATION (WEBUSE) DAN WEB CONTENT ACCESSIBILITY GUIDELINES (WCAG) 2.1 - Siti Fatimah; Ahmad Hanafi; Kharisma; Alfun Roehatul Jannah (Fakultas Teknik dan Teknologi Informasi, Universitas Jenderal Achmad Yani Yogyakarta, 2023)
The sragenkab.go.id website serves as a vital platform supporting the operations of the Sragen district government, disseminating accurate and prompt information to the public. However, various issues hamper its functionality, such as interface display problems, unclear layout, non-functional links, excessively simple design, and slow response times. To address these concerns, this study aims to evaluate the sragenkab.go.id website's usability and accessibility aspects using the Website Usability Evaluation (WEBUSE) method and the Web Content Accessibility Guideline (WCAG) 2.1 method, respectively. Using the WEBUSE method, a survey questionnaire was distributed to 100 respondents from Sragen to assess the usability level of the website. The obtained score of 0.65 indicated that the website's usability is categorized as